BIOCHAR AND TRICHOKOMPOS ORGANIC FERTILIZERS IMPROVE SOIL CHEMISTRY QUALITY AND LETTUCE VEGETABLE PRODUCTION - Yuliesi Purnawati; Suryani Suryani; Rahmawati Rahmawati; yustitia Akbar; Yunita Sabri; Desriana Desriana (JURNAL KATALISATOR, 2021)
Soil quality becomes poor with the use of inorganic chemical fertilizers and pesticides. Some efforts have been made to improve the quality of the soil, but naturally, not much has been studied. Natural improvement of soil quality by using Trichoderma and biochar and applying them to the cultivation of lettuce vegetables has not been reviewed, so it needs to be studied. This research aims to improve soil quality with Trichoderma and biochar and trial it on the cultivation of lettuce vegetable plants. The study was conducted by analyzing the chemical properties of the soil two weeks before being planted with lettuce. At the time of planting with lettuce is fertilized with Trichoderma and biochar, at the planting age of 2 weeks after planting, then the planting age after three weeks analyzed the quality of the soil again. To study the cultivation of lettuce, measurements of leaf length, plant height, Number of leaves, and plant weight at the time of harvest. The results showed an improvement in soil quality, from a soil pH of 5.52 to a pH of 7.8 N levels; 0.16%, K exchange;0.32 and P available; 4.32 ppm is better. Lettuce plants grown in soil treated with Trichoderma and biochar fertilizers showed greater yields than lettuce plants not treated with Trichoderma and biochar fertilizers. This research could improve soil quality for the foreseeable future using Trichoderma and biochar fertilizers.